Revive Pancasila: A Strategy to Foster a Generation Loyal to Pancasila in the Era of Globalization - Ety Isworo; Yoon Tae-min (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
We give thanks to the presence of God Almighty because, by His abundant grace and blessings, this course material has been compiled as a form of commitment to instill and develop the noble values of Pancasila among the younger generation, especially students. In the midst of the tide of globalization bringing various changes and challenges, it is important for us to hold firmly to the fundamental values that serve as the identity and foundation of the Indonesian nation. Pancasila — as the state foundation and national ideology — should not only serve as a formal symbol of the nation, but must become a moral guide in attitude, thought, and action. In the context of a global society, students are required not only to be intellectually and professionally capable, but also resilient in upholding Pancasila-based national values. Through this material, it is hoped that students will be able to understand, internalize, and actualize the values of Pancasila concretely in campus life, social life, and even in the global sphere. Character education based on Pancasila becomes the key in shaping a generation who are integrous, empathetic, competitive, and uphold the values of humanity, democracy, and justice. In closing, may this material become a real contribution in shaping a young generation who are not only knowledgeable, but also have noble character — as a manifestation of the true Pancasila generation.